2011
DOI: 10.1007/s10704-011-9655-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the diametral compression method for determining the tensile strength of transparent magnesium aluminate spinel

Abstract: Attempts were made to determine the inherent tensile strength of a coarse-grained, hot-pressed magnesium aluminate spinel (MgAl 2 O 4 ) using the diametral compression test. Thick (9.6 mm) disk specimens were machined from a large (356 mm square) plate of spinel. Two pairs of tungsten carbide (WC) platens, one with flat surfaces and the other with a 20 • half-arc and radius matched to the disk diameter, were used to transfer the applied load. Specimens tested using the platens with the matched radius had stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 11 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…Moreover, these results were also verified by the study by You and Su [28]. It is observed that the fracture plane is not going through the center of Brazilian discs, and these results were in good agreement with the observation of [29,30]. Changing of the flattened Brazilian disc coefficient influenced stress distribution of the flattened Brazilian disc, which had given rise to the fracture plane away from the center of Brazilian discs.…”
Section: Fracture Plane Analysis Of the Brazilian Disc Testsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, these results were also verified by the study by You and Su [28]. It is observed that the fracture plane is not going through the center of Brazilian discs, and these results were in good agreement with the observation of [29,30]. Changing of the flattened Brazilian disc coefficient influenced stress distribution of the flattened Brazilian disc, which had given rise to the fracture plane away from the center of Brazilian discs.…”
Section: Fracture Plane Analysis Of the Brazilian Disc Testsupporting
confidence: 84%
“…Both numerical simulation results and laboratory tests [28][29][30] had shown that fracture plane location would not occur along the plane going through the center of Brazilian disc, but it had more possibly gone through the compression plane ends. Thus, when adopting the Brazilian disc test to determine the tensile strength, taking the Griffith equivalent stress of Brazilian disc center as the tensile strength of rock materials would not be so accurate in the flattened Brazilian disc tests.…”
Section: Fracture Plane Analysis Of the Brazilian Disc Testmentioning
confidence: 99%
“…Over the years, this experimental technique was improved and extended to the investigation of the dynamic behaviour by applying the load at high strain-rate via a Split Hopkinson Pressure Bar setup. In the scientific literature it is possible to find a lot of works; see, for example, [8][9][10][11][12][13][14][15][16][17][18][19][20][21], in which this technique was applied to several brittle materials, among which are concrete, rocks, ceramics, glass, syntactic foams, frangible bullets, metal matrix composites, and compacted powders based materials. In most of these works, a critical analysis of the results was performed to study the real stress distribution inside the specimen which, in general, is influenced by several factors, such as the area and the way in which the load is applied, the friction and the interaction with the plates, the specimen dimensions, the presence of plastic deformation, and, obviously, the material properties.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…According to the findings of some researchers [15,16], the center of the Brazilian disc is the fracture initiation point, which was substantiated by experimental and numerical investigations. However, the investigations of some other researchers [17][18][19][20] supported that the crack initiation point was near to the loading point, away from the center. This inconsistency between both theoretical and laboratory analysis is likely to be due to the assumptions, criteria, and heterogeneity of the tested rocks.…”
Section: Introductionmentioning
confidence: 93%
“…Spider Berea sandstone Upper Devonian 120-130 [19][20][21] Spraying the paint on the front face of the sample was the final step in specimen preparation, which resulted in the black spot on the white base speckled pattern, which was prepared using Rust-Oleum flat paint ( Figure 2). The image correlation software monitored the displacement change of the applied speckled pattern and the software used the measured displacement of the speckles to calculate the full-field strain map of the sample.…”
Section: Rock Specimen Formation Permeability (Md) Porosity (%)mentioning
confidence: 99%